Managerial ownership and firms' information environment - HAN, Soongsoo (Institutional Knowledge at Singapore Management University, 2008)
We examine the relation between managerial stock ownership and the firm’s information environment. We focus on three dimensions of the information environment: total, public, and private information precision (Barron, Kim, Lim and Stevens 1998). Our results suggest that firms’ total and public information precision are positively related to managerial ownership. In contrast, there is no clear pattern in private information precision across different levels of managerial ownership. We also observe that managerial ownership has a greater impact on the firm’s public information environment after the implementation of Regulation Fair Disclosure, suggesting that the regulation was effective in improving the firms’ public information flow for firms whose managers’ interests are better aligned. Collectively, our findings suggest that one of the possible channels through which managerial ownership associates with earnings informativeness and firm value is the firms’ public information precision and that managerial incentive alignment plays an important role in how managers respond to a new disclosure regulation.